2016
DOI: 10.1186/s40679-016-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

HRTEM low dose: the unfold of the morphed graphene, from amorphous carbon to morphed graphenes

Abstract: We present experimental evidence under low-dose conditions transmission electron microscopy for the unfolding of the evolving changes in carbon soot during mechanical milling. The milled soot shows evolving changes as a function of the milling severity or time. Those changes are responsible for the transformation from amorphous carbon to graphenes, graphitic carbon, and highly ordered structures such as morphed graphenes, namely Rh6 and Rh6-II. The morphed graphenes are corrugated layers of carbon with cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 45 publications
(52 reference statements)
4
20
1
Order By: Relevance
“…The lattice fringes of thin layers revealed double layers with d-spacing of approximately 0.34 nm, which corresponded to that of a few layers graphene that was previously reported. 29 This coating has been reported that it helps in stabilizing the structure of the metal core, which enhances the durability of the metal catalyst. 30 Besides, it was also reported that the heteroatomcontaining carbon-shell, on metals enhanced the electrical conductivity, leading to the promotion of the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The lattice fringes of thin layers revealed double layers with d-spacing of approximately 0.34 nm, which corresponded to that of a few layers graphene that was previously reported. 29 This coating has been reported that it helps in stabilizing the structure of the metal core, which enhances the durability of the metal catalyst. 30 Besides, it was also reported that the heteroatomcontaining carbon-shell, on metals enhanced the electrical conductivity, leading to the promotion of the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Upon sonication, an increase in the intensity of the D and D′ bands is observed in the OLCs, implying an increase in the concentration of defects. The occurrence of D** band confirms the presence of amorphous carbon and different functional moieties in OLCs [28] , [29] , [30] . D* band, the lower energy shoulder of the D band is due to the sp 2 -sp 3 disordered graphitic lattice of the OLCs.…”
Section: Resultsmentioning
confidence: 52%
“…Few mono crystalline large sheets were also observed suggesting loss of crystallinity with increase in size of the sheets. The FFT analysis shows 6‐fold reflection spots which confirm hexagonal crystal lattice for graphene sheets with an in‐plane lattice spacing of approximately 3.1 Å, corresponding to the reflection from (002) plane …”
Section: Resultsmentioning
confidence: 86%
“…The CAP was subjected to Scholl oxidation in 2:1 AlCl 3 ‐NaCl melt at 165 °C for 6 h. The reaction mixture was quenched with water and worked up to get MG in good yields (see supporting information (SI) for details of synthesis). We have applied a variety of techniques (FTIR, UV‐Vis, XPS, Raman, XRD, TEM and AFM) for characterization of the product, and the data obtained were compared with literature to confirm our assignment of the product as graphene sheets.…”
Section: Resultsmentioning
confidence: 99%